SARS-CoV-2 Vaccination in India: Considerations of Hesitancy and Bioethics in Global Health - Mohammad Abdullah Sarkar; Ahmad Ozair; Kaushal Kishor Singh; Nishanth R Subash; Mainak Bardhan; Yashita Khulbe (Ubiquity Press, 2021)
Introduction: Worldwide mass vaccination against SARS-CoV-2, while having been the most critical action in combating further waves of COVID-19, was initially fraught with multiple infrastructural and socio-cultural challenges. Vaccine hesitancy, a phenomenon of doubt over the vaccines' claimed efficacy and/or safety amidst access to vaccination, emerged as a major challenge for global health, despite approval and regular post-marketing surveillance by major regulatory bodies. Methods: We reviewed the literature related to vaccine hesitancy in India published until November 14, 2021 using relevant keywords in various databases and examined it from a bioethical perspective. Results: Factors driving hesitancy either intensified skepticism towards vaccination in general or exacerbated reluctance towards specific vaccines. In India, hesitancy towards indigenously developed vaccines was aggravated by the lack of peer-reviewed phase III trial data before the start of vaccination, lack of public transparency of regulatory bodies, and presence of public perception of inappropriately expedited processes. This perspective piece discusses the state of mass immunization in India as a case of how vaccination and its hesitancy thereof gave rise to unique bioethical challenges in global health. In early 2021, vaccination in India was subject to difficulties in adhering to the principles of equity and justice, while a compromise of the principles of informed consent, beneficence, and non-maleficence also perhaps did occur. Conclusions: Post-pandemic debriefing on the subversion of bioethical principles will be needed, and an appropriate response may be required to rebuild and enhance the public faith in future mass vaccination movements.